Christian Nationalism and the Project of Christian Political Theory: A Review Essay of The Case for Christian Nationalism by Stephen Wolfe - DeMoor, Michael J. (Philosophia reformata, 2023)
This review essay examines Stephen Wolfe’s The Case for Christian Nationalism, focusing on his presentation of his book as a work of Christian political theory. His claims regarding national will and agency are analyzed, and problems with them are traced to his political theology and his methodological assumptions about Christian political theory. In place of those assumptions, Kuyper’s idea of architectonic critique is recommended as a more fruitful approach to Christian political theory in the Reformed tradition.